Characterization of a plasma reactor device for photovoltaic applications - Metz, Garrett Eugene, author; Williams, John D., advisor; Mahoney, Leonard, committee member; Sampath, Walajabad S., committee member; Robinson, Steve, committee member (Colorado State University. Libraries, 2012)
Heated pocket deposition (HPD) sources are used for the rapid manufacture of thin film CdS/CdTe photovoltaic devices. Standard lab devices produced at CSU by the HPD process have achieved efficiencies of 13%. New process methods are required to further improve the quality of the films, increase cell efficiency, and reduce production costs. A plasma-enhanced, close-spacing sublimation (PECSS) technique has recently been developed as a candidate process method. It has been successfully used to eliminate pin holes, to dope CdS with oxygen, and dope CdTe absorption layers; all of which have resulted in higher device efficiencies. In this work we present measurements describing the properties of the PECSS plasma. Specifically the uniformity of the ion current flux to the substrate is presented for nitrogen/oxygen and argon feed gases by means of in situ surface probes fabricated by segmenting a transparent conductive oxide film that is laid over the glass. Plasma properties within the PECSS processing chamber are also presented including plasma density, electron temperature, and plasma potential. Operational characteristics and scaling of PECSS are presented for pressures of 100-300 mTorr and surface areas of 160 - 1700 cm2. A three-dimensional model was developed to calculate plasma production and transport processes, and to gain a greater understanding of the role of energetic primaries versus bulk cold electrons on spatial ionization rates that develop within the PECSS plasma as a function of gas pressure and geometry. Comparisons between the model and experimental measurements are presented and good agreement has been observed when the appropriate spatially varying ionization rates are estimated. This work also presents the development of a diagnostic test bed that will be useful for future work in the development and understanding of the PECSS technique.